2012
DOI: 10.3109/03639045.2012.687745
|View full text |Cite
|
Sign up to set email alerts
|

Single non-ionic surfactant based self-nanoemulsifying drug delivery systems: formulation, characterization, cytotoxicity and permeability enhancement study

Abstract: Single non-ionic surfactant based self-nanoemulsifying drug delivery system (SNEDDS) was formulated and characterised for poor water soluble drug, Atorvastatin calcium. Capmul MCM oil showing highest solubility for Atorvastatin calcium was selected as oil phase. Self-nanoemulsifying capacity of Cremophor RH 40, Cremophor EL, Tween 20, Tween 60, Tween 80 and Labrasol were tested for the selected oil. In vitro dissolution studies were performed and were characterized by t85% and dissolution efficiency (DE). Cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 14 publications
2
16
0
2
Order By: Relevance
“…As depicted in Table 3, the experimental values were within or close to the wide range of values found in literature [8,9,11]. It was assumed that propylene glycol monocaprylate has greater capacity to solubilize poorly water soluble drugs due to certain polarity of caprylic acid, as discussed in the previous study with atorvastatin [47].…”
Section: Discussionsupporting
confidence: 84%
“…As depicted in Table 3, the experimental values were within or close to the wide range of values found in literature [8,9,11]. It was assumed that propylene glycol monocaprylate has greater capacity to solubilize poorly water soluble drugs due to certain polarity of caprylic acid, as discussed in the previous study with atorvastatin [47].…”
Section: Discussionsupporting
confidence: 84%
“…The zeta potential of the optimum formulation was -20.90±1.47 mV as shown in table 5. The fatty acid content in the formula may cause the negative charge of the zeta potential [41].…”
Section: Zeta Potentialmentioning
confidence: 99%
“…[22] Several studies have been published reporting MC glycerides for developing SEDDS of a wide variety of drugs. [23][24][25][26] According to these studies, being small molecular volume oil phase, medium chain glycerides showed the high solvent capacity and excellent miscibility with other surfactants and co-surfactants and enhanced the permeability and bioavailability of candidate drugs. While SCT, such as Triacetin, has not been widely explored for preparing SMEDDS.…”
Section: Original Articlementioning
confidence: 99%